Three new species in the genus Ficinia (Cyperaceae, tribe Cypereae) from the Greater Cape Floristic Region of South Africa - Muasya, A. Muthama; Stirton, Charles H. (Phytotaxa, 2022)
Despite over 300 years of botanical inventory, new species continue to be discovered within the Greater Cape Floristic Region of South Africa. Recent field work in the ecotone of the Fynbos and Succulent Karoo biomes has revealed three species of Ficinia that are new to science. Based on field observation and comparison with existing material in major herbaria, we describe and name F. bolusiana, F. stirtonii and F. swartruggensis.